Optical Spectra and Fluorescence Quenching in Azaacenes Bearing Five‐Membered Rings. Issue 9 (16th July 2019) - Hodecker, Manuel; Ganschow, Michael; Abu‐Odeh, Mahmud; Bunz, Uwe H. F.; Dreuw, Andreas
Abstract: Optical absorption and emission properties as well as fluorescence quenching via introduction of an additional unsaturated five‐membered ring in some azaacenes are investigated computationally. It is shown that non‐radiative decay via conical intersections or intersystem crossing is rather unlikely. Instead, the additional double bond alters the electronic structure of the first excited singlet state, turning it into a dark state with long lifetime and hence low fluorescence rate, that cannot be seen anymore with the naked eye. Abstract : What a difference a double bond makes : While the molecule shown here is highly fluorescent, an additional double bond at the position marked in red drastically alters the emission properties, turning the system into a non‐fluorescent one. This paper explains these different optical properties using modern computational methods.